THE EFFECT OF COMPETENCE, INTEGRITY, AND SCEPTICISM OF AUDIT PROFESSIONALS ON AUDIT QUALITY (CASE STUDY AT THE REGIONAL INSPECTORATE OF WEST BANDUNG REGENCY) - Apandi, Herdiansyah; Maruti, Djatu Retno, Silviana; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research purpose to analyze and provide empirical evidence of the effect of competence, integrity, and partial professional scepticism on audit quality. The research was conducted at the regional inspectorate of West Bandung Regency with 45 internal auditors as respondents. Data in analysis using multiple regression analysis. That t-test indicates that the competence variable has a significant positive effect on audit quality, thus if the auditor's competence is good, the resulting audit quality will also be better. The variable of integrity has a positive effect on audit quality, thus if the auditor’s integrity is good, the resulting audit quality will also be better. The variable of professional scepticism has a positive effect on audit quality, thus if the auditor's professional scepticism is good, the resulting audit quality will also be better.